Validity of the Brazilian version of the freezing of gait questionnaire - Jussara A. Oliveira Baggio; Mônica B. Curtarelli; Guilherme R. Rodrigues; Vitor Tumas (Arquivos de Neuro-Psiquiatria)
OBJECTIVE: To validate the freezing of gait questionnaire (FOG-Q) for a Brazilian population of Parkinson's disease (PD) patients. METHODS: One hundred and seven patients with a diagnosis of PD were evaluated by shortened UPDRS motor scale (sUPDRm), Hoehn and Yahr (HY), Schwab and England scale (SE), Berg balance scale (BBS), falls efficacy scale international (FES-I), gait and balance scale (GABS), and the FOG-Q Brazilian version. RESULTS: 47.7% of PD patients had FOG episodes; this group had worse scores on sUPDRSm, FOGQ, FES-I, BBS, GABS and FOG item of UPDRS when compared to the PD group without FOG. The internal consistency was 0.86, intra-rater 0.82 and inter-rater 0.78. The FOG-Q Brazilian version was significantly correlated with items related to gait and balance. The ROC curve was 0.94, the sensitivity was 0.90and specificity was 0.92. CONCLUSION: Our study suggests that the FOG-Q Brazilian version is a reliable and valid instrument for assessing FOG in PD patients.